2022
DOI: 10.1590/1413-785220223004e255534
|View full text |Cite
|
Sign up to set email alerts
|

MORTALITY IN PATIENTS > 90 YEARS OLD WITH PROXIMAL FEMORAL FRACTURES SUBJECTED TO SURGERY

Abstract: Introduction: Proximal femoral fractures have a high mortality rate among older adults, especially those aged > 80 years. Objective: To analyze predictive factors for hospital or late mortality of patients > 90 years old who showed proximal femoral fracture and subjected to surgery. Methods: The study included data from 230 patients aged > 90 years diagnosed with proximal femoral fracture and who underwent surgery between January and December 2017. The statistical evaluation was performed by mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
(18 reference statements)
0
1
0
2
Order By: Relevance
“…Diante disso, é válido ressaltar que a fratura transtrocantérica é aquela que ocorre entre a base do colo femoral até 2,5 cm distal ao trocanter menor (ALEXANDRE M, et al, 2019). Devido ao envelhecimento da população mundial, a incidência desse tipo de lesão tem aumentado consideravelmente e pondera-se que o número de casos de lesão do quadril chegará a mais de 6 milhões de casos anuais até 2050, uma vez que é mais comum em idosos (OLIVEIRA CEN, et al, 2022).…”
Section: Revisão Bibliográficaunclassified
See 1 more Smart Citation
“…Diante disso, é válido ressaltar que a fratura transtrocantérica é aquela que ocorre entre a base do colo femoral até 2,5 cm distal ao trocanter menor (ALEXANDRE M, et al, 2019). Devido ao envelhecimento da população mundial, a incidência desse tipo de lesão tem aumentado consideravelmente e pondera-se que o número de casos de lesão do quadril chegará a mais de 6 milhões de casos anuais até 2050, uma vez que é mais comum em idosos (OLIVEIRA CEN, et al, 2022).…”
Section: Revisão Bibliográficaunclassified
“…Outrossim, pacientes com idade igual ou superior a 85 anos são avaliados como um marcador independente, já que a idade elevada aumenta o risco de morte em um ano após a fratura. Logo, além das suas comorbidades, a sua idade prevalece quando se analisa a mortalidade dentro de um curto período de tempo (OLIVEIRA CEN, et al, 2022).…”
Section: Revisão Bibliográficaunclassified
“…Surgeons and patients are often hesitant to proceed with surgery due to concerns over advanced age and pre-existing comorbidities that may lead to postoperative complications and mortality 9 , 10 . While certain experts 11 , 12 particularly regarding the survival results, have indicated advantages, there is concern 13 17 among certain research that high proportion of complication rates after surgery were observed whether they had been treated surgically or conservatively. Due to multiple comorbidities, leaving hip fractures untreated can result in 1-year mortality rates of over 60% for nonagenarians and centenarians, as well as other adverse outcomes including longer length of hospital stay (LOS), frequent readmissions, and increased rates of mortality and complications 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%